Efektivitas Latihan Keterampilan Sosial pada Peningkatan Citra Diri Pasien dengan Gangguan Citra Tubuh (Post Amputasi) di RSUD Tani dan Nelayan Boalemo - Afriani R.Mahmud; Firmawati Firmawati; Nur Uyun I. Biahimo; Rini Asnawati (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2024)
Amputation results in a person becoming permanently disabled, thus bringing dramatic changes to all aspects of a person's life in daily activities which results in psychological problems that can reduce physical and socio-economic conditions because they have to adapt to the loss of parts that previously functioned normally. Therefore, to reduce body image disturbances in post-amputation patients because they cannot accept their physical condition after amputation, it is necessary to treat them with cognitive therapy, behavioral therapy, cognitive and behavioral therapy, social skills therapy and family psychoeducation. The research aims to analyze the effectiveness of social skills training in improving the self-image of patients with post-amputation body image disorders at the Tani and Fishermen Hospital, Boalemo. This research uses a quantitative research design, a pre-experimental research design with a one group pre-post test design. The population of this study was post-amputation patients at the Tani and Fishermen Hospital, Boalemo. The sample in this research consisted of 15 respondents. The data collection technique was using a questionnaire sheet to measure body image. Based on the results of the analysis, it was found that the majority were categorized as quite worse. The results of statistical tests show that the average score of the patient's self-image is 13.60 with a standard deviation of 1.033 and the average score after social skills training is 16.73 with a standard deviation of 2.815, and the p-value is 0.000 (<α 0 .05) means that social skills training is effective in improving the self-image of patients with post-amputation body image disorders at the Boalemo Farmers and Fishermen's Hospital.